Writing What Nobody Else Has Written - Janet Rodekohr (Journal of Applied Communications, 1986)
Creative writing. Sounds so exciting, so daring ... So frivolous. Does it really fit with no-frills, give-'em-the-facts crusty news reporting? Is there such a thing as noncreative writing?